Petani Kelapa Sawit dalam Bahaya: Urgensi Indonesia dalam Membantu Petani Kecil untuk Bersaing Secara Adil di Lapangan - Yenny, Oktavani; Simbolon, Putu George Matthew (CV. Social Politic Genius (SIGn), 2024)
This research is conducted to express the urgency for the Government of Indonesia to adopt a regulation concerning the protection of palm oil smallholders. Such adoption is necessary since the partnership agreement between this minor group with the non-plantation enterprise is ineffective due to the conflicting interests between the Minister of Agriculture and the Minister of Industry. To achieve this purpose, this article is written based on doctrinal research by gathering rules under the MSMEs Law, the Competition Law, the Capital Investment Law, the Job Creation Law, and the SCM Agreement. This article is also supported by the justice fairness theory by Rawls. The first discussion of this article discusses the urgency to adopt this government regulation based on the MSMEs Law and the Competition Law which is to enforce the partnership agreement. Furthermore, the second discussion analyzes the Capital Investment Law and the Job Creation Law so that this aspired law shall balance the rights and obligations of the smallholders and the non-plantation enterprise. Last but not least, the third discussion discusses what to anticipate according to the WTO rules on subsidies. In the aftermath, this article suggested next research discussing the distribution of authorities between the MOA and the MOI.